Syncronize Data Using MapReduceModel Programming - Murti Retnowo (University of Technology Yogyakarta, 2021)
Research in the processing of the data shows that the larger data increasingly requires a longer time. Processing huge amounts of data on a single computer has limitations that can be overcome by parallel processing. This study utilized the MapReduce programming model data synchronization by duplicating the data from database client to database server. MapReduce is a programming model that was developed to speed up the processing of large data. MapReduce model application on the training process performed on data sharing that is adapted to number of sub-process (thread) and data entry to database server and displays data from data synchronization. The experiments were performed using data of 1,000, 10,000, 100,000 and 1,000,000 of data, and use the thread as much as 1, 5, 10, 15, 20 and 25 threads. The results showed that the use of MapReduce programming model can result in a faster time, but time to create many thread that many require a longer time. The results of the use of MapReduce programming model can provide time efficiency in synchronizing data both on a single database or a distributed database.